Handbook for evaluating infrastructure regulatory systems - Brown, Ashley C.; Ashley C.Brown ...[et.al] ("Washington, D.C", 2006)
This handbook provides an analytical framework and supporting instruments for evaluating the performance of new infrastructure regulators in developing countries. It argues that an evaluation must examine both regulatory governance (the ""how"" of regulation) as well as regulatory substance (the ""what"" of regulation). If the evaluation is to produce useful ""second generation"" reforms, it must examine how formal elements of the regulatory system have been implemented in practice and the effect of these elements on sector performance. It describes how to ""operationalize"" the independent regulator model and elements of possible transitional regulatory systems. Examples are generally drawn from electricity regulation but the analytical framework, questionnaires and interview protocols can be easily adapted to other infrastructure sectors.
Keywords: Electric utilities-Government policy-Developing countrie